Electricity Power Monitoring Based on Internet of Things - Saputra, Ekky Haqindytia; Ma'arif, Alfian; Alayi, Reza (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
Every year, electricity consumption in Indonesia has increased in line with population growth and the national economy. One of the factors causing an increase in electricity consumption in Indonesia, one of which is caused by the lifestyle of modern society which is wasteful in using electricity. Modern society is increasingly using electricity inefficiently. One potential solution to this problem is the use of the Internet of Things (IoT) concept. The Internet of Things, or IoT for short, is a system of connected computing devices whose sole purpose is to maximize the benefits of an internet connection. The system built using the PZEM-004T sensor which is processed by the Arduino Uno microcontroller will be sent to Wemos D1 Mini via serial communication (TX-RX) so that it can be displayed on the BLYNK New IoT application on a smartphone. As for the parameters that will be displayed in the BLYNK application, namely voltage, current, and power usage of electrical devices. By using this application, users will be able to more easily and effectively monitor and how much electrical energy is used by equipment remotely. This equipment has been tested from September to October, on 5 electronic devices such as lights, TVs, refrigerators, rice cookers, fans with satisfactory results, namely being able to monitor the use of electrical devices using smartphones through the blynk application.